2013
DOI: 10.1242/jcs.131144
|View full text |Cite
|
Sign up to set email alerts
|

Cut via CrebA transcriptionally regulates the COPII secretory pathway to direct dendrite development inDrosophila

Abstract: SummaryDendrite development is crucial in the formation of functional neural networks. Recent studies have provided insights into the involvement of secretory transport in dendritogenesis, raising the question of how the secretory pathway is controlled to direct dendritic elaboration. Here, we identify a functional link between transcriptional regulatory programs and the COPII secretory machinery in driving dendrite morphogenesis in Drosophila dendritic arborization (da) sensory neurons. MARCM analyses and gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 59 publications
2
52
0
Order By: Relevance
“…The number of filopodial extensions correlates to the level of Cut expression, corresponding to our findings. It was recently shown that Cut-dependent filopodia formation depends on the function of CrebA, which activates components of the secretory pathway (Iyer et al, 2013;Fox et al, 2010). Cut might not only orchestrate membrane organization through the modulation of the secretory pathway, it also directly controls cytoskeletal dynamics (Iyer et al, 2012;Nagel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The number of filopodial extensions correlates to the level of Cut expression, corresponding to our findings. It was recently shown that Cut-dependent filopodia formation depends on the function of CrebA, which activates components of the secretory pathway (Iyer et al, 2013;Fox et al, 2010). Cut might not only orchestrate membrane organization through the modulation of the secretory pathway, it also directly controls cytoskeletal dynamics (Iyer et al, 2012;Nagel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In class III sensory neurons, outposts exist in both single-and multi-compartment forms. 57 In class I neurons, however, although the Golgi structural protein GM130 is present in the dendrites, 79 only medial-Golgi markers were detected. 20,55 The transcription factor Dar1 is required to create complex dendrite arbor structures.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…Loss of Abrupt leads to Cnn downregulation and the decoupling of microtubule nucleation from Golgi outposts, thereby causing an increase in anterograde microtubule nucleation events and the de-repression of branching. 20 In another transcriptional pathway, Cut, which promotes dendrite branching, 41,73 regulates Sec31 and other components of the COPII secretory transport pathway to promote Golgi outpost formation 79 (the outcome on dendrite microtubule nucleation was not examined).…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…The homeobox transcription factor cut is expressed at increasing levels in class II, IV, and III, and overexpression of cut in a class II cell transforms its arbor to a class IV morphology (Grueber et al 2003a). Cut levels specify distinct morphologies by providing an increasing abundance of proteins that direct branch morphogenesis and stabilization (Iyer et al 2013, Sulkowski et al 2011. Cut also leads to formation of the actin-rich dendritic spikes typical of class III da neurons by elevating levels of effectors such as Fascin, an actin-bundling protein (Nagel et al 2012).…”
Section: Figurementioning
confidence: 99%